Indirect Nanoplasmonic Sensing Study of Z907 Dye Molecules Interacting with TiO2 Films for Dye Sensitized Solar Cell Applications - Nkurunziza, Emmanuel (My University, 2014)
In todays society, increasing demand to switch to renewable energy has triggered the scientific community to have a deep interest in the Dye Sensitized Solar Cell (DSSC), which is thought to be one of the future's reliable sources of solar energy because of its low cost and simple manufacture compared to conventional semiconductor photovoltaics (PV). Still, at the molecular level, many of the phenomena crucial for the DSSC optimum performance are not well understood and this has had a consequence of a very small improvement in the performance of the device in the last two decades (until a recent breakthrough by using solid - state sensitizers). Nanotechnology has provided plasmonics-based sensors such as Indirect Nanoplasmonic Sensing (INPS), which are effective for studying the dye adsorption process (one of the core phenomena for the functioning of a DSSC) with high sensitivity, in situ, and in real time. In this thesis, INPS was used to investigate the real time adsorption and desorption of dye (Na/Z907) molecules on flat TiO2 surfaces, which mimic the cathode of the DSSC. From the INPS real time adsorption/desorption kinetics, values of rate constants and equilibrium adsorption constants were obtained. They are in agreement with the ones obtained when Langmuir isotherms of the equilibrium coverage for different concentration were used. The existence of loosely bound dye molecules has been experimentally proven by a series of intermittent adsorptions and desorption cycles. These experiments showed a decreased desorption rate after each adsorption-desorption cycle, which is explained by removal of the loosely bound molecules during each rinsing step to promote the reorganization of the dye molecules on the surface and thereby increasing its stability. Finally, a method to calculate the number of dye molecules adsorbed/desorbed was successfully adapted, which allowed the interpretation of the achieved quality of the dye layer formed in terms of dye molecules per unit surface that would participate in electricity generation in a real DSSC.
Keywords: Nanovetenskap och nanoteknik; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Nanoteknik; Nanoscience & Nanotechnology; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Nano Technology